Method for the regeneration of magnetic materials used in magnetic removal of microplastics from aqueous matrices

JP2025504690APending Publication Date: 2025-02-14CAPTOPLASTIC SL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024545229
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-27
Filing Date
2023-01-26
Publication Date
2025-02-14

Smart Images

  • Figure 2025504690000012
    Figure 2025504690000012
  • Figure 2025504690000013
    Figure 2025504690000013
  • Figure 2025504690000014
    Figure 2025504690000014
Patent Text Reader

Abstract

The present invention relates to a process for breaking down microplastic / magnetic material agglomerates, which makes it possible both to recover the magnetic material and to obtain microplastics free of magnetic material. The invention essentially consists in breaking down the magnetic material / microplastic agglomerates by treatment with a concentrated aqueous salt solution, followed by separation of both types of solids by density and / or by application of a magnetic field.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for the regeneration of magnetic materials used in the magnetic separation of microplastics from aqueous matrices. This process also makes it possible to obtain microplastics free of magnetic materials. The invention essentially consists in breaking down the magnetic material / microplastic aggregates by treatment with a concentrated aqueous salt solution, followed by separation of both types of solids by density and / or by application of a magnetic field. [Background technology]

[0002] Due to the excellent properties of plastics, among which the ease of molding, high mechanical and chemical resistance, and low cost stand out, plastics are widely used both in industry and society as a whole. Since the development of the first synthetic polymers in the mid-20th century, the production of these synthetic polymers has not stopped growing. In 2019, the global production of plastics reached 370 million tons (PlasticsEurope, 2020), and the production of plastics is expected to double in the next 20 years (MacArthur, DE et al., The New Plastics Economy: Rethinking the Future of Plastics. World Economic Forum. (2016)). Although plastics are certainly useful, the generation of plastic waste and its improper management are significant environmental issues.

[0003] Removal of plastics is not a problem when the plastics are large in size. However, with use, plastics decompose, producing smaller pieces of plastic that are more difficult to remove (especially when the pieces have a diameter of millimeters). Microplastics are defined as plastic particles with a size of less than 5 mm (Bergmann, M. et al., Marine Anthropogenic Litter (2015) Springer) and are traces of plastics that are widely present in the environment. Microplastics have been found in virtually all ecosystems on Earth, including inland and marine waters, sediments, air, and soil (Grbic, J. et al., Environmental Science and Technology Letters 6 (2019) 68-72). They are therefore present in living organisms (Cole, M. et al., Nature Scientific Reports 4: 4528 (2014) 1-8; Wieczorek, A. M. et al., Environmental Science and Technology 53 (2019) 5387-5396), essentially aquatic organisms, so there is considerable concern about the potential damage their presence could have both in humans and in fauna (Wright, S. Let al., Environmental Science and Technology 51 (2017) 6634-6647; Cox, K. D. et al., Environmental Science and Technology 53 (2019) 7068-7074).

[0004] According to recent studies (ES 2 796 998 A1 and WO 2020 / 240069 A1 as well as Grbic, J. et al., Environmental Science and Technology Letters, 6 (2019) 68-72), the separation of microplastics from water is very effective, regardless of the nature and size of the microplastics, by interaction with magnetic particles and subsequent application of a magnetic field. This method has great advantages compared to traditional filtration methods, but it involves a relatively high consumption of magnetic material and inevitably generates waste (microplastic / magnetic particle aggregates). On the other hand, when using magnetic separation as a method to analyze microplastics present in an aqueous matrix, the generation of microplastic / magnetic material aggregates leads to an increase in the density of the microplastics, which limits the subsequent density separation of said microplastics from the rest of the solids present in the water (and which would have interacted with the magnetic material). Similarly, the subsequent characterization of the microplastics is also hindered, since the microplastics form part of the aggregates and the magnetic material may interfere with the analysis. So far, no process could be found in the literature that would allow breaking down microplastic / magnetic material aggregates and separating both types of solids. This could be the reason why magnetic separation of microplastics from water for quantification and characterization has not been studied so far. This is also an important limitation in the large-scale use of this technology in water treatment.

[0005] Taking into account the background, the development of a process that allows breaking down the formed microplastic / magnetic material agglomerates and separating both types of solids regardless of their composition and size in an efficient, rapid, environmentally friendly and cost-effective manner would be an important finding in the field. Summary of the Invention

[0006] The inventors have surprisingly found that it is possible to break down the microplastic / magnetic iron material aggregates and thus separate both types of solids. This separation is useful, for example, to facilitate the subsequent characterization of the microplastics. It is also useful to achieve the regeneration of the magnetic iron material so that it can be reused in water treatment systems. The separation of magnetic aggregate forming components is a rather interesting subject that has not been reported in the literature so far. The inventors have unexpectedly found that by introducing these microplastic / magnetic iron material aggregates into a high concentration salt solution, it is possible to break down the interactions that bind them to each other and thus to completely separate the magnetic iron material from the microplastics.

[0007] As shown in the examples, the microplastic / magnetic iron material aggregates were degraded very efficiently, achieving a recovery yield of more than 99.0% regardless of the nature and size of the plastic. Moreover, the recovered microplastics were completely free of magnetic material. The process of the present invention is particularly advantageous since it also allows the decomposition of non-plastic organic solid particle / magnetic iron material aggregates, achieving a recovery yield of magnetic material of more than 99.0% regardless of the nature and size of the non-plastic organic solid particles. Characterization of the recovered magnetic material made it possible to confirm that the solids did not sustain significant changes in their composition, size and crystallinity. In fact, the recovered magnetic iron material was used again in the system without any loss of potency being observed. Another further advantage of the process of the present invention is that all the reagents used are environmentally friendly. It is likewise important to point out the simplicity of the equipment required and the low cost of the materials and reagents used. Finally, the method showed a high reproducibility of the results obtained.

[0008] Thus, in a first aspect, the present invention provides a process for degrading magnetic ferrous material / organic particle agglomerates, preferably microplastic / magnetic ferrous material particle agglomerates, comprising: a) providing a magnetic ferrous material / organic particle agglomerate, preferably a microplastic / magnetic ferrous material particle agglomerate; b) introducing the agglomerates of step a) into an aqueous salt solution for breaking up the agglomerates, the salt of the aqueous salt solution being selected from the group consisting of NaH2PO4, Na2HPO4, Na3PO4, NaCl, NaI, ZnBr2, ZnCl2, and mixtures thereof, and the concentration of the salt of the aqueous salt solution being in the range of 10 g / L to 1000 g / L; c) optionally separating the magnetic ferrous particles from the organic particles by applying a magnetic field and / or by density separation; The present invention relates to a process comprising:

[0009] In a second aspect, the present invention relates to a process for breaking down magnetic ferrous material / organic particle agglomerates according to the first aspect, further comprising characterisation of the organic particles and / or recovery of the magnetic ferrous material. [Brief description of the drawings]

[0010] [Figure 1] Particle size distribution of magnetic iron mineral (magnetite) used in the examples. [Diagram 2] Optical microscope images of PS (250–500 μm) / magnetic material aggregates before (left) and after (right) treatment with concentrated NaH2PO4 solution. [Diagram 3] Scanning electron microscope images of PS (250–500 μm) / magnetic material aggregates before (left) and after (right) treatment with concentrated NaH2PO4 solution. [Figure 4] Scanning electron microscope images of PET (100–250 μm) / magnetic material aggregates before (left) and after (right) treatment with concentrated NaH2PO4 solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] A first aspect of the present invention is a process for breaking down magnetic ferrous material / organic particle agglomerates, preferably microplastic / magnetic ferrous material particle agglomerates, comprising: a) providing a magnetic ferrous material / organic particle agglomerate, preferably a microplastic / magnetic ferrous material particle agglomerate; b) introducing the agglomerates of step a) into an aqueous salt solution for breaking up the agglomerates, the salt of the aqueous salt solution being selected from the group consisting of NaH2PO4, Na2HPO4, Na3PO4, NaCl, NaI, ZnBr2, ZnCl2, and mixtures thereof, and the concentration of the salt of the aqueous salt solution being in the range of 10 g / L to 1000 g / L; c) optionally separating the magnetic ferrous particles from the organic particles by applying a magnetic field and / or by density separation; The present invention relates to a process comprising:

[0012] Step a) consists in providing a magnetic ferrous material / organic particle agglomerate, preferably a microplastic / magnetic ferrous material particle agglomerate.

[0013] In a preferred embodiment, in step a) microplastic / magnetic ferrous material particle agglomerates and magnetic ferrous material / non-plastic organic particle agglomerates are provided.

[0014] In another preferred embodiment, in step a) a microplastic / magnetic iron material particle agglomerate is provided.

[0015] The magnetic iron material / organic particle agglomerates, preferably the microplastics / magnetic iron material particle agglomerates, may for example have been obtained according to the processes described in documents ES 2 796 998 A1 and WO 2020 / 240069 A1.

[0016] In the context of the present invention, the term "microplastic" or "microplastics" refers to plastic material having an average diameter of less than 5 mm, preferably comprised within the range of 0.1 μm to 5 mm, more preferably within the range of 0.1 μm to 1 mm, even more preferably within the range of 0.1 μm to 500 μm, even more preferably within the range of 100 μm to 500 μm, even more preferably within the range of 100 μm to 250 μm. The size of microplastics can be determined by scanning electron microscopy, for example using the conditions described in the examples. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The average diameter is defined as the average length of the microplastic particles (the sum of the lengths of the analyzed particles out of the number of particles analyzed).

[0017] Microplastics can be formed from any plastic material, preferably synthetic organic polymers, such as polyethylene terephthalate (PET), polyethylene (PE), including high density polyethylene (HDPE) and low density polyethylene (LDPE), polyvinyl chloride (PVC), polypropylene (PP), polystyrene (PS), polycarbonate (PC), polyurethane (PU), and combinations thereof.

[0018] "Polyethylene terephthalate" or "PET" is a polymer obtainable by the reaction of polycondensation between terephthalic acid and ethylene glycol. Polyethylene terephthalate has the following structure: [ka]

[0019] "Polyethylene" or "PE" refers to a polymer obtainable by the polymerization of ethylene. Polyethylene has the following structure: [ka]

[0020] "High density polyethylene" or "HDPE" refers to polyethylene whose density falls within the range of 0.930 to 0.970 g / mL. "Low density polyethylene" or "LDPE" refers to polyethylene whose density falls within the range of 0.917 to 0.930 g / mL.

[0021] "Polyvinyl chloride" or "PVC" refers to a polymer obtainable by polymerization of vinyl chloride. Polyvinyl chloride has the following structure: [ka]

[0022] "Polypropylene" or "PP" refers to a polymer obtainable by polymerization of propylene. Polypropylene has the following structure: [ka]

[0023] "Polystyrene" or "PS" refers to a polymer obtainable by polymerization of styrene. Polystyrene has the following structure: [ka]

[0024] "Polycarbonate" or "PC" refers to a polymer containing functional groups linked by carbonate groups (-O-C=O)-O-), such as diallyldiethylene glycol polycarbonate or, most commonly, bisphenol A polycarbonate, the structure of which is shown below. [ka]

[0025] "Polyurethane" or "PU" refers to a polymer obtained by condensation of a polyol, among which ethylene glycol and propylene glycol stand out, with a polyisocyanate, among which methylene diphenyl diisocyanate (MDI) and toluene diisocyanate (TDI), resulting in urethane groups (-NH-(C=O)-O-) in the structure of the polymer. Polyurethanes are widespread due to the range of polyisocyanates and polyols that can be used to form them.

[0026] In a preferred embodiment, the microplastics are selected from the group consisting of polyethylene terephthalate (PET), polyethylene (PE) including high density polyethylene (HDPE) and low density polyethylene (LDPE), polyvinyl chloride (PVC), polypropylene (PP), polystyrene (PS), polycarbonate (PC), polyurethane (PU), and mixtures thereof; more preferably, selected from the group consisting of polystyrene, polypropylene, polyethylene terephthalate, high density polyethylene, low density polyethylene, and mixtures thereof; even more preferably, selected from the group consisting of polystyrene, polypropylene, polyethylene terephthalate, and mixtures thereof; even more preferably, selected from the group consisting of polystyrene, polypropylene, polyethylene terephthalate, and mixtures thereof; most preferably, selected from the group consisting of polystyrene, polypropylene, and mixtures thereof. An advantage of the process of the present invention is its universal nature, since the magnetic iron material / microplastic aggregates are efficiently degraded regardless of the chemical nature of the microplastics.

[0027] In a particular embodiment, the microplastics are selected from the group consisting of polystyrene, polypropylene, polyethylene terephthalate, and mixtures thereof, having a size in the range of 100 μm to 500 μm, preferably 100 μm to 250 μm.

[0028] The term "magnetic iron material" refers to any natural or synthetic solid substance that contains at least one iron species and has magnetic properties, i.e., is attracted by a magnet. In certain embodiments, the magnetic iron material is inorganic. In certain embodiments, the magnetic iron material is uncoated, i.e., bare magnetic material particles. Preferably, the magnetic iron material has a molecular weight of between 5 emu / g and 100 emu / g (5·10 3 A / m and 10 5 A / m), more preferably between 30 emu / g and 90 emu / g (30·10 3 A / m and 90·10 3 A / m), and even more preferably between 65 emu / g and 90 emu / g (65·10 3 A / m and 90·10 3 A / m), most preferably between 70 emu / g and 90 emu / g (70·10 3 A / m and 90·10 3 The magnetic properties of the magnetic iron material can be determined using a magnetometer equipped with a SQUID (Superconducting Quantum Interference Device) sensor. The magnetization (M) of the magnetic iron material is measured at room temperature in the range of -10000 to 10000 Oe (corresponding to -797700 to 797700 A / m) depending on the applied external magnetic field (H). The magnetic saturation value of the material is the value of M reached when any subsequent increase in H does not cause an increase in the magnetization of the material. Preferably, the iron material has an iron content of at least 10% by weight, preferably at least 20% by weight, more preferably at least 25% by weight, even more preferably at least 30% by weight, even more preferably at least 35% by weight, even more preferably at least 40% by weight, even more preferably at least 45% by weight, even more preferably at least 50% by weight, even more preferably at least 55% by weight, even more preferably at least 60% by weight, even more preferably at least 65% by weight. The percentage of iron can be determined using a total reflection X-ray fluorescence (TXRF) spectrometer using the method described in the Examples.

[0029] Preferably, the magnetic iron material comprises an iron species selected from the group consisting of Fe(II), Fe(III), metallic Fe, and mixtures thereof. Examples include magnetite (formed by ferrous oxide-ferric oxide FeO·Fe2O3, sometimes formulated as Fe3O4), maghemite (γ-Fe2O3), ilmenite (FeTiO3), and pyrrhotite (Fe 0.8-1 In a preferred embodiment, the magnetic iron material is the mineral magnetite.

[0030] The use of magnetic iron minerals, and in particular magnetite, is advantageous from an economic and environmental standpoint, as it is an abundant, environmentally friendly material that is easily separated from the aqueous matrix.

[0031] The magnetic iron material is in the form of particles. The term "particles" refers to magnetic iron material in the form of powder or granules with an average diameter of less than 5 mm, preferably comprised between 0.05 μm and 5 mm, more preferably between 0.05 μm and 1 mm, even more preferably between 0.05 μm and 500 μm, even more preferably between 0.05 μm and 100 μm, even more preferably between 0.1 μm and 10 μm, even more preferably between 0.1 μm and 5 μm, even more preferably between 0.1 μm and 1 μm, even more preferably between 0.1 μm and 0,5 μm, most preferably between 0.1 μm and 0.3 μm. Preferably, the particle size distribution must be sufficiently narrow in the established size range. The determination of the particle size and distribution of the magnetic iron material can be carried out, for example, by scanning electron microscopy using the conditions described in the examples. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The average diameter is defined as the average length of the longest dimension of each magnetic ferrous material particle (the sum of the lengths of the analyzed particles out of the number of particles analyzed). For determining the particle size distribution, it is appropriate to use the statistics D10, D50, and D90, which capture 10%, 50%, and 90% of the accumulated particles by volume. In the preferred range, D10 (indicating that 10% of the particles in the sample by volume have a diameter smaller than this value) is 0.3 μm or less, D50 (indicating that 50% of the particles in the sample by volume have a diameter smaller than this value, representing the average particle size) is 0.50 μm or less, and D90 (indicating that 90% of the particles in the sample by volume have a diameter smaller than this value) is 0.8 μm or less. In the most preferred ranges, D10 (indicating that 10% by volume of the particles of the sample have a diameter smaller than this value) is 0.15 μm or less, D50 (indicating that 50% by volume of the particles of the sample have a diameter smaller than this value, representing the average particle size) is 0.20 μm or less, and D90 (indicating that 90% by volume of the particles of the sample have a diameter smaller than this value) is 0.35 μm or less. The magnetic iron material particles can be obtained by crushing the material and then sieving it into the size ranges mentioned above.The size of the magnetic ferrous material particles refers to the average diameter of the particles determined in dry conditions, without taking into account agglomeration of the magnetic material particles when suspended in an aqueous matrix.

[0032] The term "microplastic / magnetic ferrous particle aggregates" or "microplastic / magnetic ferrous particle aggregates" refers to clusters of particles formed by, preferably due to interactions between, microplastics and magnetic ferrous particles. Similarly, the term "organic particle / magnetic ferrous particle aggregates" or "organic / magnetic ferrous particle aggregates" refers to clusters of particles formed by, preferably due to interactions between, organic particles (non-microplastic) and magnetic ferrous particles. Similarly, the term "non-plastic organic particle / magnetic ferrous particle aggregates" or "non-plastic organic / magnetic ferrous particle aggregates" refers to clusters of particles formed by, preferably due to interactions between, non-plastic organic particles and magnetic ferrous particles. This interaction is a physicochemical interaction; there is an effective fixation between the surfaces of both substances such that the aggregates remain intact despite agitation or modification of the water properties (temperature, pH), but no changes in chemical structure were observed.

[0033] The expression "non-plastic organic particles" or "non-plastic organic solid particles" refers to particles that can have any shape, whose average diameter is in the range of 0.1 μm to 1 cm, preferably 0.1 μm to 5 mm, 0.1 μm to 5 mm, preferably 0.1 μm to 1 mm, more preferably 0.1 μm to 500 μm, even more preferably 100 μm to 500 μm, even more preferably 100 μm to 250 μm, that are not made of plastic material, and whose average diameter is the average length (sum of the lengths of the analyzed particles out of the number of analyzed particles), and whose length is the largest dimension of each particle. Examples of plastics are the same as those described for microplastics. Examples of non-plastic (organic) material particles are of plant origin (leaves, branches, seeds, fruits, etc.), of animal origin (bones, microcrustaceans, larvae, animal remains, etc.), of fungal origin, etc. The size of the particles can be determined in the same way as described for microplastics.

[0034] The expression "organic particles" includes both "non-plastic organic particles" and "microplastics" as defined above.

[0035] In certain embodiments, the organic particles are selected from the group consisting of microplastics, non-plastic organic particles, and mixtures thereof, preferably microplastics.

[0036] Next, step b) is carried out by introducing the agglomerates of step a) into an aqueous salt solution to break up the agglomerates, the salt of the aqueous salt solution being selected from the group consisting of NaH2PO4, Na2HPO4, Na3PO4, NaCl, NaI, ZnBr2, ZnCl2, and mixtures thereof, and the salt concentration of the aqueous salt solution is in the range of 10 g / L to 1000 g / Ls.

[0037] In a preferred embodiment, the salt of the aqueous salt solution of step b) is selected from the group consisting of NaH2PO4, Na2HPO4, Na3PO4, NaCl, NaI, ZnCl2, and mixtures thereof; more preferably, selected from the group consisting of NaH2PO4, Na2HPO4, Na3PO4, NaCl, NaI, and mixtures thereof; even more preferably, NaH2PO4, NaCl or NaI, and even more preferably, NaH2PO4.

[0038] Preferably, the concentration of the salt (single salt / salts) of the aqueous salt solution of step b) is selected based on the solubility of the salt (single salt / salts) used in water. The concentration of the concentrated aqueous salt solution is at least 10 g / L. Preferably, the concentration of the concentrated aqueous salt solution is in the range of 10 g / L to 1000 g / L, preferably 100 g / L to 1000 g / L, more preferably 300 g / L to 1000 g / L, even more preferably 300 g / L to 900 g / L, even more preferably 500 g / L to 900 g / L, most preferably 700 g / L to 900 g / L.

[0039] In certain embodiments, the aqueous salt solution is an aqueous solution of a salt selected from the group consisting of NaH2PO4, Na2HPO4, Na3PO4, and mixtures thereof, with a salt concentration between 500 g / L and 900 g / L.

[0040] In certain embodiments, the aqueous salt solution is an aqueous solution of NaCl, with a NaCl concentration between 100 g / L and 360 g / L.

[0041] In another particular embodiment, the aqueous salt solution is an aqueous solution of NaI, with a NaCl concentration between 150 g / L and 600 g / L.

[0042] In a preferred embodiment, the aqueous salt solution is an aqueous solution of NaH2PO4 with a concentration of 700 g / L to 900 g / L.

[0043] In a preferred embodiment, the concentration of the aggregates introduced into the aqueous salt solution in step b) is between 1 mg / L and 2000 g / L.

[0044] In a preferred embodiment, the mixture obtained in step b) is subjected to stirring, which promotes the interaction of the microplastic / magnetic iron material aggregates with the concentrated aqueous salt solution. The stirring can be carried out by any conventional method known to the person skilled in the art, such as mechanical, magnetic or ultrasonically assisted stirring, more preferably ultrasonically assisted stirring.

[0045] In a preferred embodiment, the time required to break down the microplastic / magnetic iron material aggregates using the aqueous salt solution of step b) is in the range of 1 second to 24 hours, more preferably 1 second to 12 hours, even more preferably 1 second to 6 hours, even more preferably 1 second to 1 hour, and most preferably 1 minute to 30 minutes.

[0046] In certain embodiments, the process of the present invention is carried out discontinuously, i.e., in batches.

[0047] In another particular embodiment, the process of the present invention is carried out continuously.

[0048] The next step, step c), is optional and consists in separating the magnetic ferrous particles from the organic particles by applying a magnetic field and / or by density separation.

[0049] In a preferred embodiment, step c) is performed.

[0050] In this step, the mixture obtained in step b) is subjected to separation by density and / or by applying a magnetic field to separate the clean microplastics in the supernatant.

[0051] In a preferred embodiment, step c) is performed, in which the magnetic ferrous particles are separated from the organic particles by density.

[0052] In another embodiment, step c) is performed, in which the magnetic ferrous material particles are separated from the organic particles by applying a magnetic field.

[0053] In another embodiment, step c) is carried out, in which the magnetic ferrous material particles are separated from the organic particles by density and by applying a magnetic field.

[0054] In a preferred embodiment, the mixture obtained in step b) is left to stand and then the clean microplastics in the supernatant are removed by filtration thereof, in particular by vacuum filtration.

[0055] Preferably, the mixture obtained in step b) is left to stand and a magnetic field is simultaneously applied to the lower part of the container containing it, and then the clean microplastics in the supernatant are removed by filtration thereof, in particular by vacuum filtration.

[0056] In a particular embodiment, the mixture obtained in step b) is allowed to stand for a period of time ranging from 1 minute to 24 hours, more preferably from 1 minute to 12 hours, even more preferably from 1 minute to 6 hours, even more preferably from 1 minute to 1 hour, and most preferably from 1 minute to 30 minutes.

[0057] In certain embodiments, step c) is not performed.

[0058] In a particular embodiment, all steps of the process of the present invention are carried out at a temperature in the range of 5-95°C, preferably 10-30°C, more preferably 20-25°C.

[0059] The microplastics obtained in step c) can be subjected to further steps of characterization with the aim of knowing their composition, size and / or shape.Similarly, the magnetic material obtained in step c) can be recovered and reused for the separation of microplastics from aqueous matrices, such as for example in the processes described in documents ES 2 796 998 A1 and WO 2020 / 240069 A1.

[0060] Microplastics can be characterized by various techniques in order to determine their composition (Fourier transform infrared (FTIR) spectroscopy and / or Raman spectroscopy), size (optical microscopy and / or scanning electron microscopy or dynamic light scattering (DLS)), and shape (optical microscopy and / or scanning electron microscopy).

[0061] As shown in the examples, the recovered microplastics are completely free of magnetic material, and recovery yields of magnetic material of over 99.0% were achieved, regardless of the nature and size of the non-plastic organic solid particles. In a particular embodiment of the first aspect of the invention, at least 40% of the microplastics were recovered; in another particular embodiment, at least 50% of the microplastics were recovered; in a preferred embodiment, at least 70% of the microplastics were recovered; and in the most preferred embodiment, at least 90% of the microplastics were recovered. Characterization of the recovered magnetic material allowed to confirm that the solids did not sustain significant changes in their composition, size and crystallinity. In fact, the recovered magnetic iron material was used again in the system without any loss of potency being observed.

[0062] Therefore, in a second aspect, the present invention relates to a process for breaking down magnetic ferrous material / organic particle agglomerates according to the first aspect, further comprising characterisation of the organic particles and / or recovery of the magnetic ferrous material.

[0063] In a further aspect, the present invention relates to the use of the process for breaking down magnetic ferrous material / organic particle agglomerates according to the first aspect for characterisation of the organic particles and / or recovery of the magnetic ferrous material.

[0064] Illustrative examples are set forth below to disclose the features and advantages of the present invention, but they should not be construed as limiting the scope of the invention as defined in the claims. EXAMPLES

[0065] Materials and Methods Determining the particle size and shape of microplastics In the present invention, microplastics were added to an aqueous matrix and then subjected to magnetic separation by the process described herein. The particle size range of the microplastics was pre-determined by sieving using different size sieves (5 mm, 1 mm, 500 μm, 250 μm, 100 μm, 50 μm, 20 μm).

[0066] For size measurements of microplastics, a Nikon Eclipse Ci-S / Ci-L upright optical microscope equipped with a DS-Fi2 digital camera and a DS-U3 control unit, with software for measuring and processing images (NIS-Elements L Imaging), was used. A JEOL JSM 6335F scanning electron microscope with amplification from 10x to 500,000x was also used. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The shape of the microplastics is analyzed by observing images of the particles at different magnifications.

[0067] Determining the composition of microplastics The composition of the microplastics was determined by Fourier transform infrared spectroscopy (FTIR). The microplastic samples were analyzed according to the conventional analytical method using KBr pellets. Pellets were prepared by adding 1 mg of the microplastic sample and approximately 99 mg of KBr. The resulting powder mixture was compressed by applying a pressure of 10 tons by a hydraulic press to obtain KBr pellets. The samples were then analyzed using a Spectrum Two spectrophotometer (Perkin Elmer). The transmission test was performed at 4000-450 cm -1 The spectra obtained were compared to a library database to determine the type of polymer forming the microplastics using Perkin Elmer Spectrum Software.

[0068] Determination of particle size of magnetic ferrous materials The particle size (mean diameter) and particle distribution of the magnetic ferrous material were determined by scanning electron microscopy analysis of the dry material. The instrument used was a JEOL JSM 6335F with amplification from 10x to 500,000x. The length and width of the magnetic ferrous material particles were measured and assigned a size of the largest dimension (length). For the determination of particle size distribution, it is appropriate to use the statistics D10, D50, D90, which capture 10%, 50%, and 90% by volume of the accumulated particles.

[0069] Determination of iron percentage The iron content of the magnetic ferrous material was determined using a total reflection X-ray fluorescence (TXRF) spectrometer, i.e., S2 Picofox (Bruker) model equipped with a molybdenum source. The sample preparation method consisted of open vessel digestion of the sample with a solution of hydrochloric, nitric and hydrofluoric acids in a volume ratio of 6:2:0.5 at 105 °C for 1.5 hours. The concentration of the material in the vessel was 1000 mg / L and a total volume of 10 mL was used. If necessary, the magnetic ferrous material was pre-ground to a size of less than 100 μm. Once the material sample was digested, an internal gallium standard was added to the solution for later quantification. A 3 μL aliquot of the resulting solution was introduced into the analytical spectrometer and run at 50 kV and 600 μA with an acquisition time of 500 seconds. Integration of the peak corresponding to iron in the resulting spectrogram allowed the weight percentage of iron contained in the material to be determined.

[0070] X-ray diffraction Identification and characterization of the crystalline phases present in the magnetic iron material was performed using powder X-ray diffraction (PXRD). Samples were analyzed on a Panalytical X'Pert PRO theta / theta diffractometer equipped with a Cu tube (Kα radiation, 8.04 keV). The diffractometer has a secondary graphite monochromator and a Xe gas detector. Theta / 2theta scans were performed in the 2θ range of 10-80°, with an angle increment of 0.04°, and an accumulation time of 4 seconds. Prior to analysis, magnetic iron material particles were milled to a size of less than 100 μm, if necessary. High Score Plus software and the ICDD (International Centre for Diffraction Data) PDF-4 Full File crystallography database were used to identify the crystalline phases present in the obtained diffractograms.

[0071] Determining magnetic saturation The magnetic properties of the magnetic iron materials were measured using a Quantum Design MPMS XL-5 magnetometer equipped with a SQUID (Superconducting Quantum Interference Device) sensor. If necessary, the magnetic iron materials were pre-ground to a size smaller than 100 μm. The magnetic moment (M) of the magnetic iron materials is −10,000 to 10,000 Oe (−797,700 to 797,700 A m in SI) at room temperature. -1 The magnetic saturation value is the value of M reached when any subsequent increase in H does not cause an increase in the magnetization of the material.

[0072] Example 1. Degradation of microplastic / magnetic iron aggregates by treatment with concentrated salt solutions Experiments to break down microplastic / magnetic iron material agglomerates were carried out after the formation of said agglomerates, obtained according to the processes described in documents ES 2 796 998 A1 and WO 2020 / 240069 A1. Specifically, 20 mg of microplastics and 40 mg of magnetic iron mineral in a volume of 20 mL of water with a solid chloride concentration of 0.1 g / L and pH 7 were used. The microplastics, the magnetic iron mineral, and the water were introduced into a glass vial. The suspension was mechanically stirred for 30 seconds using a paddle stirrer. A magnetic field generated by a magnet was then applied to separate the agglomerates and the free magnetite. Three types of microplastics were used: polystyrene (PS), polypropylene (PP), and polyethylene terephthalate (PET). Similarly, two microplastic particle size ranges were tested: 100-250 μm and 250-500 μm. The separation process was carried out using magnetic iron mineral, namely crushed magnetite (having an average particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline nature of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of magnetic iron mineral used was in the range of 68-78% by weight. In turn, the magnetic saturation value of the material was in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0073] The separation of polystyrene, polypropylene, and polyethylene terephthalate microplastics was greater than 99.0%. Similarly, more than 99.9% of the added magnetite was also removed from the water. The magnetically separated solids, especially the microplastic / magnetic material agglomerates, which were clearly distinguishable by their larger size (100-250 μm and 250-500 μm), were then subjected to a process to break down the agglomerates.

[0074] The microplastic / magnetic material aggregates were then placed in 20 mL of concentrated salt solution (NaH2PO4, 850 g / L, density 1.35 g / cm 3The samples were resuspended in 1000 mL of 10 ...

[0075] Table 1 shows the results obtained by disintegrating microplastic / magnetic material aggregates with different sizes and plastic types, taking into account the clean (magnetic material-free) microplastic recovery rate. Figures 2 and 3 show optical and scanning electron microscope images, respectively, of microplastic / magnetic material aggregates before and after being subjected to treatment with a concentrated salt solution containing 250-500 μm PS microplastics. Similarly, Figure 4 shows scanning electron microscope images, respectively, of microplastic / magnetic material aggregates before and after being subjected to treatment with a concentrated salt solution containing 100-250 μm PET microplastics.

[0076] The microplastics / magnetic material aggregates were degraded very efficiently, achieving recovery yields of more than 99.0% regardless of the nature and size of the plastics. The recovered microplastics were completely clean, as shown in Figures 2, 3 and 4, which show optical and scanning electron microscope images, respectively. In that sense, their surfaces did not show the presence of magnetic material in any case, which is a good example of the effectiveness of the treatment developed to degrade the microplastics / magnetic material aggregates.

[0077] It is important to emphasize that during the treatment to break up the aggregates, the leaching of iron from the magnetic material is completely negligible (<0.1 mg / L).

[0078] [Table 1]

[0079] The procedure detailed in Example 1 was followed, but with varying salt solution concentrations, e.g., concentrations of NaH2PO4 aqueous solution (0.5, 10, 100, 500 and 850 g L -1 By changing the concentration of fluorine, a decomposition experiment of microplastic magnetic iron material aggregates using the process of the present invention was also carried out using PS with sizes of 250 to 500 μm as the microplastic.

[0080] Table 2 shows the recovery of clean microplastics (free of magnetic material) obtained from the degradation of microplastic-magnetic material aggregates (PS and Fe3O4 with sizes between 250 and 500 μm) at different salt concentrations. As can be seen, the percentage of clean microplastics recovered is 10 g L -1 At a NaH2PO4 concentration of 500 g L -1 At a salt concentration of 850 g L -1 Virtually quantitative recoveries were obtained at salt concentrations of 0.01 to 0.05%. These results indicate that recovery can be performed over a wide range of salt concentrations.

[0081] [Table 2]

[0082] Next, the effect of salt in the salt solution was evaluated. The microplastic / magnetic material aggregates were immersed in 20 mL of NaCl or NaI solution (NaCl: 360 g / L, density 2.16 g / cm 3 ;NaI:460g / L, density 3,67g / cm 3) after 2 min. The samples were mechanically shaken vigorously for 15 min and then placed in an ultrasonic bath for an additional 20 min. After the experiment, the suspended particles located at the top of the vial were collected with a pipette and the rest of the vial contents were filtered. All solids that had settled to the bottom of the vial were removed. Both the suspended particles (mainly microplastics) and the settled particles (mainly ferromagnetic materials) were simply washed using deionized water to remove traces of salts from the surface of the particles. All assays were performed in triplicate.

[0083] Table 3 shows the results obtained for the disruption of microplastic / magnetic material aggregates by NaCl and NaI salt solutions.

[0084] [Table 3]

[0085] Example 2. Disintegration of non-plastic organic solid particle / magnetic ferrous material agglomerates by treatment with concentrated salt solutions The experiments to break down the non-plastic organic solid particles / magnetic iron material agglomerates were carried out after the experiments of magnetic separation of the particles according to the same process described in Example 1. 20 mg of non-plastic organic solid particles and 40 mg of magnetic iron mineral in a volume of 20 mL were used. Three types of non-plastic organic solid particles in water were used: pine needles, elm leaves, and mimosa leaves. In all cases, crushed leaves sieved using a sieve with the mesh opening diameter in the size range of 100-250 μm were used. The separation process was carried out using magnetic iron mineral, namely crushed magnetite (having an average particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline nature of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of magnetic iron mineral used was in the range of 68-78% by weight. The magnetic saturation value of the material was then in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0086] The separation of non-plastic organic solid particles from the water exceeded 99.0%. Similarly, over 99.9% of the added magnetite was also removed from the water. The magnetically separated solids, especially the non-plastic organic solid particles / magnetic material agglomerates, which are clearly distinguishable by their larger size (100-250 μm), were then subjected to a process to break down the agglomerates.

[0087] The non-plastic organic solid particles / magnetic material aggregates were dissolved in 20 mL of concentrated salt solution (NaH2PO4, 850 g / L, density 1.35 g / cm 3 The samples were mechanically stirred vigorously for 15 minutes and then introduced into an ultrasonic bath for another 20 minutes. After the experiment, the suspended particles located at the top of the vial were collected with a pipette and the remaining contents of the vial were subjected to filtration. This removed all solids that had settled at the bottom of the vial. Both the suspended particles (basically organic particles) and the settled particles (basically magnetic materials) were washed with deionized water with the aim of removing salt residues from the surface of the particles. All tests were performed in triplicate and at room temperature (20-25 °C).

[0088] Table 4 lists the results obtained for breaking down the non-plastic organic solid particle / magnetic ferrous material agglomerates, taking into account the clean (magnetic ferrous material free) non-plastic organic solid particle recovery rates.

[0089] The non-plastic organic solid particle / magnetic ferrous material agglomerates were decomposed very efficiently, achieving recovery yields of over 99.0% regardless of the nature and size of the non-plastic organic solid particles.

[0090] It is important to emphasize that during the treatment to break up the aggregates, the leaching of iron from the magnetic material is completely negligible (<0.1 mg / L).

[0091] [Table 4]

[0092] Example 3. Reuse of magnetic iron material recovered by treating the magnetic fraction obtained in the separation of polystyrene microplastics contained in a synthetic aqueous matrix with a concentrated salt solution

[0093] After experiments of magnetic separation of polystyrene microplastics with a size range of 100-250 μm contained in a synthetic aqueous matrix, experiments were carried out to reuse the magnetic iron material. The process described in Example 1 was followed using 20 mg of microplastics and 40 mg of magnetic iron mineral in a volume of 20 mL to cause the formation of microplastic / magnetic iron material aggregates. The separation process was carried out using magnetic iron mineral, namely crushed magnetite (having an average particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline nature of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of magnetic iron mineral used was in the range of 68-78% by weight. The magnetic saturation value of the material was then in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0094] Separation of polystyrene microplastics from a synthetic aqueous matrix was carried out by forming microplastic / magnetic iron material aggregates and applying a magnetic field. The microplastic separation yield was greater than 99.0%. Similarly, more than 99.9% of the added magnetite was also removed from the water. All magnetically separated solid particles were then subjected to a process to break down the aggregates according to the process described in Example 1.

[0095] Concentrated saline solution (NaH2PO4, 850g / L, density 1.35g / cm 3The magnetite recovered after treatment with ) was washed with copious amounts of deionized water and dried (12 h at 60 °C). It was then used again for the separation of polystyrene microplastics with a size range of 100-250 μm from a synthetic aqueous matrix. A volume of 20 mL of 20 mg of microplastics and 40 mg of recycled magnetic iron mineral were used, following the process described in Example 1. The results obtained are listed in Table 5. [Table 5]

[0096] The recycled magnetic iron material was able to achieve the same polystyrene microplastic separation yield as the fresh magnetic iron material, which confirms the feasibility of the developed recovery process. It is also important to highlight that during the treatment, the leaching of iron from the magnetic material was completely negligible (<0.1 mg / L). Likewise, the characterization of the recovered magnetic iron material allowed to confirm that the minerals did not undergo significant changes in their composition, size and crystallinity.

Claims

1. 1. A process for breaking down magnetic ferrous material / organic particle agglomerates comprising the steps of: a) providing said magnetic ferrous material / organic particle agglomerate; b) introducing the agglomerates of step a) into an aqueous salt solution for breaking up the agglomerates, the salt of the aqueous salt solution being NaH 2 P.O. 4 , Na 2 H.P.O. 4 , Na 3 P.O. 4 , NaCl, NaI, ZnBr 2 , ZnCl 2 and mixtures thereof, wherein the concentration of said salt in said aqueous salt solution is in the range of 10 g / L to 1000 g / L; c) optionally separating the magnetic ferrous particles from the organic particles by density and / or by applying a magnetic field; A process including.

2. 2. The process of claim 1, wherein the organic particles are microplastics.

3. 3. The process of claim 2, wherein the microplastics are selected from the group consisting of polystyrene (PS), polypropylene (PP), polyethylene terephthalate (PET), polyethylene (PE) including high density polyethylene (HDPE) and low density polyethylene (LDPE), polyvinyl chloride (PVC), polycarbonate (PC), polyurethane (PU), and mixtures thereof, preferably selected from the group consisting of polystyrene, polypropylene, polyethylene terephthalate, and mixtures thereof.

4. 4. The process according to any of claims 1 to 3, wherein said organic particles have a size in the range of 0.1 μm to 5 mm, preferably 0.1 μm to 1 mm, more preferably 0.1 μm to 500 μm, more preferably 100 μm to 500 μm, even more preferably 100 μm to 250 μm.

5. The salt of the aqueous salt solution of step b) is NaH 2 P.O. 4 5. The process of claim 1, wherein the aqueous solution is selected from the group consisting of NaCl, NaI and mixtures thereof.

6. The process according to any of claims 1 to 5, wherein the salt concentration of the aqueous salt solution of step b) is in the range of 100 g / L to 1000 g / L.

7. The process of any of claims 1 to 6, wherein the magnetic iron material comprises an iron species selected from the group consisting of Fe(II), Fe(III), metallic Fe, and mixtures thereof.

8. 8. The process of claim 7, wherein the magnetic iron material is magnetite.

9. The process according to any of the preceding claims, wherein the average diameter of the magnetic ferrous material is comprised between 0.1 μm and 10 μm.

10. 10. The process of claim 9, wherein the average diameter of the magnetic ferrous material is comprised between 0.1 μm and 0.3 μm.

11. The process according to any of claims 1 to 10, wherein the concentration of aggregates introduced into the aqueous salt solution in step b) is between 1 mg / L and 2000 g / L.

12. The process according to any of claims 1 to 11, wherein the mixture resulting from step b) is subjected to stirring.

13. A process according to any of the preceding claims, wherein step c) is carried out, preferably in step c) the magnetic ferrous particles are separated from the organic particles by density.

14. A process according to any preceding claim, further comprising characterisation of said organic particles and / or recovery of said magnetic ferrous material.